Patient-specific 3D models aid planning for triplane proximal femoral osteotomy in slipped capital femoral epiphysis. (April 2017) - Cherkasskiy, L.; Caffrey, J. P.; Szewczyk, A. F.; Cory, E.; Bomar, J. D.; Farnsworth, C. L.; Jeffords, M.; Wenger, D. R.; Sah, R. L.; Upasani, V. V.
Purpose: Slipped capital femoral epiphysis (SCFE) can result in a complex three-dimensional (3D) deformity of the proximal femur. A three-plane proximal femoral osteotomy (TPFO) has been described to improve hip mechanics. The purpose of this study was to evaluate the benefits of using 3D print technology to aid in surgical planning. Patients and Methods: Fifteen children treated with TPFO for symptomatic proximal femoral deformity due to SCFE were included in this study. Ten patients were treated by a single surgeon with (model group, n = 5) or without (no-model group, n = 5) a 3D model for pre-operative planning, and compared with patients treated by two senior partners without the use of a model (senior group, n = 5) to evaluate for a learning curve. Peri-operative data including patient body mass index (BMI), surgical time and fluoroscopy time were recorded. Results: Children in all three groups had similar BMIs at the time of the TPFO. Post-operative radiographic parameters were equally improved in all three groups. On average, surgical time decreased by 45 minutes and 38 minutes, and fluoroscopy time decreased by 50% and 25%, in the model group compared with the no-model and senior groups, respectively. Conclusions: Patient-specific 3D models aid in surgical planning for complex 3D orthopaedic deformities by enabling practice of osteotomies. Results suggest that 3D models may decrease surgical time and fluoroscopy time while allowing for similar deformity correction. These models may be especially useful to overcome steep learning curves for complex procedures or in trainee education through mock surgical procedures.